Baret en pak voor Den Uyl's eredoctoraat aan de UvA. Diverse graflinten voor Liesbeth en Joop den Uyl
Baret en pak voor Den Uyl's eredoctoraat aan de UvA. Diverse graflinten voor Liesbeth en Joop den Uyl.